2003
DOI: 10.1037/0021-9010.88.5.836
|View full text |Cite
|
Sign up to set email alerts
|

Which comes first: Employee attitudes or organizational financial and market performance?

Abstract: Employee attitude data from 35 companies over 8 years were analyzed at the organizational level of analysis against financial (return on assets; ROA) and market performance (earnings per share; EPS) data using lagged analyses permitting exploration of priority in likely causal ordering. Analyses revealed statistically significant and stable relationships across various time lags for 3 of 7 scales. Overall Job Satisfaction and Satisfaction With Security were predicted by ROA and EPS more strongly than the rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
419
4
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(463 citation statements)
references
References 47 publications
30
419
4
10
Order By: Relevance
“…Prior studies reported that organizations having values such as cohesiveness, empowerment, and participatory decision-making are likely to create an environment that fosters employee satisfaction. Satisfied employees were found to relate positively to organizational performance (Ryan, Schmit, & Johnson, 1996;Schneider, Hanges, Smith, & Salvaggio, 2003) and even customer satisfaction (Harter, Schmidt, & Hayes, 2002). Thus, the employee is one of the top priorities that cooperative should take into consideration if the statements were to be reviewed.…”
Section: Content Priorities Of Cooperatives Mission Statementsmentioning
confidence: 99%
“…Prior studies reported that organizations having values such as cohesiveness, empowerment, and participatory decision-making are likely to create an environment that fosters employee satisfaction. Satisfied employees were found to relate positively to organizational performance (Ryan, Schmit, & Johnson, 1996;Schneider, Hanges, Smith, & Salvaggio, 2003) and even customer satisfaction (Harter, Schmidt, & Hayes, 2002). Thus, the employee is one of the top priorities that cooperative should take into consideration if the statements were to be reviewed.…”
Section: Content Priorities Of Cooperatives Mission Statementsmentioning
confidence: 99%
“…research on interrelations and levels of coherence between business strategies and particular subfunctions of HRM with company's performance results (Beer et al, 1984;Schuler and Jackson, 1987;Wright and Snell, 1991;Guest, 1997;Chanda andShen, 2009, Guest et al, 2011;Stor, 2011), and · behavioral results -e.g. employee attitudes, employee engagement and satisfaction, employee and/ or managerial interpersonal relations (Wright et al, 1994;Nagy, 2002;Schneider, 2003;Farr and Tran, 2008;Rich et al, 2010;Juchnowicz, 2010;Ferguson and Reio, 2010;Suchodolski, 2014;Juchnowicz, 2014;Sparrow et al, 2016).…”
Section: The Measureable Role Of Hrm In Company's Successmentioning
confidence: 99%
“…research on the links and degree of coherence between business strategies and particular HRM subfunctions with company results (Beer et al, 1984;Schuler & Jackson 1987;Wright & Snell, 1991;Guest 1997;Chanda, Shen, 2009, Guest et al, 2011Stor, 2011), · behavioral results-e.g. employee attitudes, their engagement, satisfaction, interpersonal relations, creativity (Wright et al, 1994;Nagy, 2002;Schneider, 2003;Farr, Tran, 2008;Rich et al, 2010;Juchnowicz, 2010;Suchodolski, 2014;Juchnowicz, 2014;Sparrow et al, 2016).…”
Section: The Theoretical Background Of the Studymentioning
confidence: 99%